2017
DOI: 10.1017/s1751731116001944
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of organoleptic quality and composition of beef from suckler bulls from different production systems

Abstract: Bull beef production is traditionally based on high concentrate rations fed indoors. Inclusion of grazed grass, which is generally a cheaper feed, would decrease the cost of bull beef production, but may affect beef quality. Accordingly, the organoleptic quality and composition of beef from continental-sired suckler bulls (n=126) assigned to either ad libitum concentrates to slaughter (C), grass silage (GS) ad libitum for 120 days followed by C (GSC) or GS followed by 100 days at pasture and then C (GSPC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…Sensory analysis was carried out using a 10-person trained taste panel, using panellists selected for their sensory acuity. The LT samples were thawed overnight at 4°C, cut into 20 mm thick steaks and grilled on pre-coded foil-lined grill pans under preheated, domestic low level grills, turning every 3 min until the desired centre temperature of 74°C (measured by a thermocouple probe at the geometrical centre of the sample) was reached; a detailed procedure is given in Mezgebo et al (2017).…”
Section: Proximate Composition and Sensory Analysesmentioning
confidence: 99%
“…Sensory analysis was carried out using a 10-person trained taste panel, using panellists selected for their sensory acuity. The LT samples were thawed overnight at 4°C, cut into 20 mm thick steaks and grilled on pre-coded foil-lined grill pans under preheated, domestic low level grills, turning every 3 min until the desired centre temperature of 74°C (measured by a thermocouple probe at the geometrical centre of the sample) was reached; a detailed procedure is given in Mezgebo et al (2017).…”
Section: Proximate Composition and Sensory Analysesmentioning
confidence: 99%
“…Post slaughter, carcasses were weighed and graded for conformation according to the 95 EU Beef Carcass Classification Scheme as described in Mezgebo et al (2016). At 1 h 96 post-slaughter, a sample (ca.…”
Section: Carcass Grading and Muscle Tissue Collection 94mentioning
confidence: 99%
“…However, producing 51 beef from suckler bulls, which usually involves provision of a high concentrate ration for 52 a prolonged period, is usually less profitable because of the higher cost of concentrates 53 compared to grass silage or grazed grass diets (Finneran et al, 2011). Incorporating a 54 grazing period prior to finishing on a concentrate diet has been shown to reduce the 55 production costs of LM suckler bulls (O'Riordan et al, 2011) with little impact on eating 56 quality of the beef (Mezgebo et al, 2016). 57…”
Section: Introduction 46mentioning
confidence: 99%
See 1 more Smart Citation
“…O'Riordan et al (2012) described a modified sytem to improve the economics of bull beef production which incorporated a grass silage-based indoor winter feeding period followed by a grazing period prior to finishing indoors on a high concentrate ration. Mezgebo et al (2016) reported that compared to the traditional system, the modified grass-based system led to a decrease in intramuscular fat concentration and collagen solubility associated with a decrease in tenderness, flavour liking and overall liking of the beef. A feature of the modified grassbased bull production system is the exploitation of compensatory growth (Hornick et al 2000) at pasture subsequent to the winter feeding phase.…”
Section: Introductionmentioning
confidence: 99%